2018
DOI: 10.3390/nu10091322
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet among School Children and Adolescents Living in Northern Italy and Unhealthy Food Behaviors Associated to Overweight

Abstract: The purposes of this study were to evaluate the differences in Mediterranean diet and its components among primary and secondary school children and adolescents living in northern Italy, and the associations with the weight status. Adherence was assessed by the KIDMED (Mediterranean Diet Quality Index) questionnaire on 669 subjects (6–16 years) attending five schools of Novara. The adherence was poor in 16.7%, average in 63.7%, and high in 19.6% of the students. Poor adherence was more frequent in primary than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
72
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 41 publications
25
72
3
3
Order By: Relevance
“…Numerous systematic reviews and meta-analyses attribute a lower incidence of diseases and a better health to fish consumption [51,52], but few relate this to a better body composition in adolescents. Although the consumption of fish, together with vegetables and fruit, seems to be a pending task in adolescence, the results found for N-O waist boys coincide with similar studies where children and adolescents had a regular consumption of fish [35,38]. On the other hand, although more research is needed to examine the types of dairy products in relation to the risk of childhood and adolescent overweight, the accumulated evidence from studies suggests that dairy consumption is associated inversely and longitudinally with the risk of overweight and obesity in these ages [53,54].…”
Section: Kidmed Index and Responses In Boys And Girl With And Withoutsupporting
confidence: 86%
See 1 more Smart Citation
“…Numerous systematic reviews and meta-analyses attribute a lower incidence of diseases and a better health to fish consumption [51,52], but few relate this to a better body composition in adolescents. Although the consumption of fish, together with vegetables and fruit, seems to be a pending task in adolescence, the results found for N-O waist boys coincide with similar studies where children and adolescents had a regular consumption of fish [35,38]. On the other hand, although more research is needed to examine the types of dairy products in relation to the risk of childhood and adolescent overweight, the accumulated evidence from studies suggests that dairy consumption is associated inversely and longitudinally with the risk of overweight and obesity in these ages [53,54].…”
Section: Kidmed Index and Responses In Boys And Girl With And Withoutsupporting
confidence: 86%
“…In this aspect, the MD is revealed to be an appropriate dietary pattern [17]. Most recently reviewed studies conducted in southern European countries reported that approximately half the children and adolescents show a low adherence to MD [38]. The participants of the current study presented a medium level of adherence to the MD (5-6) [39].…”
Section: Kidmed Index and Responses In Boys And Girl With And Withoutmentioning
confidence: 49%
“…MD has justified its efficacy in the primary and secondary prevention of cardiovascular diseases, with the highest level of scientific evidence [43]. In addition to this, it has recently been demonstrated that better adherence to the MD is associated with a better lipid profile and adiposity measures and, in the case of women, with the reduction of some cardiovascular risk factors [44]. In spite of these enormous health benefits, among the participants of the current study, it is observed that only one out of four presents an optimal adherence to the MD.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of fish, nuts and dairy products, representing a fundamental aspect in the MedDiet, can be related to a better body composition and fitness performance in adolescents, in terms of speed/agility and cardiorespiratory endurance [23]. Nonetheless, even in European countries surrounding the Mediterranean Sea, half of the children and adolescents show only a low adherence to this healthy dietary tradition [24], with a high rate of pediatric overweight and development of obesity and related complications in adult life. Rising obesity rates will contribute to large healthcare expenditure increases, and this would require future cost containment efforts through large-scale health promotion programs and weight loss interventions, fostering a combination of diet quality changes and physical activity [25].…”
mentioning
confidence: 99%